Islamic Educational Values in the Verses of the Song “Mars Nahdlatul Wathan” by TGKH. Muhammad Zainuddin Abdul Madjid from Lombok - Ulyan Nasri; Muzakkir Walad; Muhammad Zainul Ansori (International Journal of Sociology of Religion, 2023)
This research aims to analyze the Islamic educational values embedded in the verses of the song "Mars Nahdlatul Wathan" written by TGKH. Muhammad Zainuddin Abdul Madjid. This study employs a literature analysis method to comprehend the meaning and messages conveyed in the song lyrics and to identify the Islamic educational values reflected in its verses. The research findings indicate that "Mars Nahdlatul Wathan" contains several highly relevant Islamic educational values. Firstly, the song emphasizes the importance of unity, solidarity, and harmony in society, values that are greatly emphasized in Islam. Secondly, the song encourages the preservation and love for the nation and homeland, in accordance with Islamic teachings on patriotism. Thirdly, it underscores the significance of education and knowledge enhancement as a means to advance society, aligning with Islamic teachings on the importance of knowledge and education. Lastly, the song calls for striving for the welfare of society, reflecting the values of jihad in Islam, not only in a physical sense but also in the sense of working for the common good. Thus, this research concludes that "Mars Nahdlatul Wathan" by TGKH. Muhammad Zainuddin Abdul Madjid contains several Islamic educational values that can serve as a guide for the community in understanding and practicing Islamic teachings in daily life and in building a better society.